Jovens, imaginário de paz e televisão - Salles, Vera Lúcia Rolim (2008)
This thesis deals with the role television plays in the process of socialization young people, focusing the relation between youths and imaginary of peace and the messages transmitted in the soap operas and TV news. This study we carried through individual interviews complemented with the technique of informal quarrel with focal groups to inquire a number of 15 to 24 year-old young people (living of the Village Embratel, a neighborhood of the city of São Luís, capital of the state of Maranhão), about the soap opera Duas Caras and TV news Jornal Nacional . The results of this study show that, these young, even so already bring their own idea of peace, and recognize it in both the soap opera and the TV news; they disclose that the speech of the violence is the one that predominates in these televising sorts. On one hand, this thesis adverts the creators of TV programs to the fundamental role young people have in construction of social imaginary TV programs have in the construction of the social imaginary, particularly in the contemporary societies. This could constitute one of the criteria for the election of the messages to be transmitted for the television, particularly, the soap operas and TV news. On the other hand, it points the absence of research in the area of Social Sciences that approach this theme